PENGETAHUAN LOKAL DAN PEMANFAATAN KRATOM DI DESA GURUNG KECAMATAN SEBERUANG KABUPATEN KAPUAS HULU - Herawatiningsih, Ratna; Resti, Brigita Novita; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2025)
Kratom is a type of endemic plant originating from Kalimantan which has been used traditionally for a long time. This research aims to examine local knowledge and explore the characteristics of the community in using kratom in Gurung Village. The benefits of this research are expected to be able to provide information regarding local knowledge and use of kratom in Gurung Village. The method used is a survey method with a census technique, namely by conducting interviews with all kratom farmers, it is known that the total number of kratom farmers is 23 people. Based on the age characteristics of the respondents who own and manage kratom land in this village, most are in the age group between 16-64 years (86.96%) where in this case the respondents are in a productive age. There are three local knowledge and uses of kratom studied, namely knowledge, norms and beliefs. The knowledge of the Gurung Village community regarding the use of kratom includes properties, habitat types, forest area determination, cultivation techniques, harvesting, post-harvest processes, processing, marketing and selling prices. The norms that apply in the use of kratom are that it is prohibited to pick kratom leaves during menstruation, it is forbidden to take kratom that grows around other people's yards or gardens without the permission of the owner because it can be subject to customary sanctions. the belief that there is that is presented at the time of gawai Dayak, and has the belief of pruning a kratom tree that is already tall. Keywords: Gurung Village, kratom, local knowledge. Abstrak Kratom merupakan salah satu jenis tumbuhan endemik yang berasal dari Kalimantan yang sejak dahulu sudah dimanfaatkan secara tradisional. Penelitian ini bertujuan untuk mengkaji pengetahuan lokal dan menggali karakteristik masyarakat dalam pemanfaatan kratom di Desa Gurung. Manfaat dari penelitian ini diharapkan mampu memberikan informasi mengenai pengetahuan lokal dan pemanfaatan kratom di Desa Gurung. Metode yang digunakan adalah metode survei dengan teknik sensus yaitu dengan melakukan wawancara terhadap seluruh petani kratom, diketahui bahwa jumlah dari seluruh petani kratom berjumlah 23 orang. Berdasarkan karakteristik usia responden yang memiliki dan mengelola lahan kratom di desa ini paling banyak berada dalam kelompok usia antara 16-64 tahun (86,96%) dimana dalam hal ini responden berada pada usia yang produktif. Pengetahuan lokal dan pemanfaatan kratom yang diteliti ada tiga yaitu pengetahuan, norma dan keyakinan. Pengetahuan masyarakat Desa Gurung terhadap pemanfaatan kratom meliputi khasiat, jenis habitat, penentuan kawasan hutan, teknik budidaya, pemanenan, proses pasca panen, pengolahan, pemasaran dan harga jual. Norma yang berlaku dalam pemanfaatan kratom yaitu dilarang memetik daun kratom pada saat datang bulan, dilarang mengambil kratom yang tumbuh disekitaran pekarang rumah atau kebun orang lain tanpa seijin dari pemiliknya karena bisa dikenakan sanksi adat. keyakinan yang ada yaitu disajikan pada saat gawai dayak, dan memiliki kepercayaan memangkas pohon kratom yang sudah tinggi. Kata kunci: Desa Gurung, Kratom,Pengetahuan lokal.